Higiene, Sanitasi, dan Cemaran Escherichia Coli pada Serombotan di Pasar Senggol Kecamatan Klungkung, Kabupaten Klungkung - Ni Wayan Arya, Utami; A.A Bulan, Ginitri; I Made, Subrata; Wijaya Putra, Anak Agung Ngurah Dwi Ariesta (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPA, 2024)
Food safety issues are the most common in traditional foods. The application of sanitation and hygiene is very important in creating healthy and safe food for humans. The culinary sector must pay attention to hygiene and sanitation to maintain public health. Food contamination can cause food to become a source of dangerous diseases and diseases caused by food are called foodborne-disease. Serombotan is one of the traditional Balinese culinary delights that is popular with the community. As a traditional culinary, there is no SOP (Standard Operating Procedure) in terms of raw materials and the process of making Serombotan. This makes hygiene and sanitation in Serombotan important. This study aims to determine the relationship between hygiene, sanitation and E.coli contamination with Serombotan which is sold in the senggol market, Klungkung sub- district, Klungkung regency. The research method used was an analytic research design with a cross sectional approach. In this study, laboratory tests were carried out on E.coli contamination on Serombotan and traders' handswabs. Laboratory tests showed that all Serombotan and Handswab samples contained E.coli bacteria. The Chi-Square test on the hygiene of traders with E.coli contamination in Serombotan showed no relationship. Observations made on the hygiene of traders showed that 91.67% of traders had clean and short nails and did not use nail polish. Sanitation of trade locations with E.coli contamination in Serombotan shows no relationship. The sanitation of Serombotan trading locations shows that all trade routes that allow traders to access safe water as well as latrines/toilets that can be used by traders as well as trading locations are flood free. Storage and packaging equipment sanitation with E.coli contamination in Serombotan also showed no relationship. Observations on the sanitation of storage and packaging equipment showed that 100% of the conveyances/carts and storage containers were in good condition, clean and able to protect food. There is a significant relationship between E.coli contamination in group traders and E.coli contamination in Handswabs. Hand hygiene is very influential against various contaminants. In this study, 91.67% of Serombotan traders did not use gloves or tools such as spoons or tongs to pick up cooked food.